‘Our war is with words’: Dora Marsden, egoism, and literary modernism - Haughton, T (2023)
This thesis examines the development of egoism in Dora Marsden’s three journals – The Freewoman (1911-1912), the New Freewoman (1913), and The Egoist (1914) – and situates Marsden’s philosophy within the development of literary modernism. Informed by the advancements of modernist periodical studies, this thesis returns canonical modernists, including T. S. Eliot, James Joyce, and Ezra Pound, to their original publishing contexts in the periodical form. I argue that reading canonical modernists in their pre-canonical form facilitates a reassessment of our understanding of modernist individualism. Chapter one offers an overview of the three journals and charts the development of egoist philosophy from The Freewoman to The Egoist. Current critical opinion separates the feminist ideology of The Freewoman from the literary interests of the New Freewoman and The Egoist. In contrast, this chapter traces a coherent narrative of intellectual development in Marsden’s thought across all three iterations. Chapter two compares The Freewoman’s use of literature to the position of literature in the New Freewoman after the imagist group are introduced. It argues that imagism’s introduction to the Marsden journals does not represent a point of rupture. Instead, it argues that imagism was welcomed into the New Freewoman because of a pre-existing association between literature and individualism. This argument is supported by a reading of Dorothy Richardson’s interactions with The Freewoman. Chapter three examines Marsden’s attempt to develop an egoistic linguistics in comparison to the linguistic experiments of James Joyce, whose A Portrait of the Artist as a Young Man was serialised in The Egoist alongside Marsden’s early editorials on language. It argues that Joyce’s egoistic linguistics exposes an intersubjective potential in Marsden’s egoism. Chapter four charts the final developments of the egoism of The Egoist during T. S. Eliot’s time as assistant editor. It argues that situating Eliot’s work in the context of The Egoist reveals a reliance on individual subjective viewpoints that transforms Eliot’s poetics of impersonality into a poetics of intersubjectivity.